Handel's last chance - Pownall, Leon.; Fennell, Tod.; Parkes, Gerard; McKenna, Seanna; Jones, Cody.; Miller, Steven; Rockett, Jennifer; Devine, David; Devine Entertainment Corporation; Alef Studio; Sony Classical Film & Video ([New York, N.Y.] : Sony Classical Film & Video, 2003)
With his career failing, Handel needed a big hit. A young thief with a wonderful voice lands in jail and Handel secures his release so that the boy can perform in the first performance of "Messiah.
DVD.
English, Spanish, French.
Closed captioned.
Title from disc.
Leon Pownall, Tod Fennell, Gerard Parkes, Seana McKenna, Cody Jones, Steven Miller, Jennifer Rockett.
Music, George Frederic Handel ; creators/story, David Devine and Richard Mozer ; co-producer, Jan Oparty ; director of photography, David Perrault ; editor, Michael Pacek ; writer, Marlene Matthews ; producers, Richard Mozer, David Devine ; director, Milan Cheylov.
Keywords: Handel, George Frideric, -- 1685-1759. -- Drama; Handel, George Frideric, -- 1685-1759 -- Drama; Handel, George Frideric, -- 1685-1759. -- idex; Biographical films; Feature films; Biographical films; Video recordings for the hearing impaired; Biographical -- Feature